An investigation of the influence of stakeholder factors affecting the success of the implementation of inclusive education in Malawi primary schools: A case study of four primary schools in Zomba district - Francis Lingolwe; Grames Wellington Chirwa (Journal of Interdisciplinary Sciences)
Malawi has focused on providing special educational services, especially for children with visual and hearing impairments in specialized schools. Children with relatively minor learning difficulties, such as slow learners, that is children who are slow in grasping concepts and who require a bit of time before they can understand things have not been provided with special academic support. This study was therefore conducted to determine the influence of stakeholders factors in the implementation of inclusive education in mainstream primary schools affecting the success of the implementation of inclusive education. Four mainstream primary schools and thirty-four participants were involved in this study. The results of the study indicated that the implementation of inclusive education is facing a number of stakeholder factors which act as barriers to effective implementation of inclusive education in mainstream primary schools in the studied schools. These factors include, inadequate funding from the Ministry of Education for effective implementation of inclusive education, lack of specialist teachers to support general education teachers in the mainstream schools, lack of provision of infrastructure suitable for learners with different special needs in the mainstream schools and lack of provision of special needs textbooks and other special needs instructional materials in the mainstream schools by the national education curriculum development centre in Malawi, the Malawi Institute of Education and fifthly, lack of provision of orientation training on inclusive education to school head teachers (principals) and mainstream teachers by the Ministry of Education. The study has thus made recommendations on how to improve the implementation of inclusive education in the mainstream primary schools in the country.